1992
DOI: 10.1038/ng1292-324
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA deletions in human brain: regional variability and increase with advanced age

Abstract: We have examined the role of somatic mitochondrial DNA (mtDNA) mutations in human ageing by quantitating the accumulation of the common 4977 nucleotide pair (np) deletion (mtDNA4977) in the cortex, putamen and cerebellum. A significant increase in the mtDNA4977 deletion was seen in elderly individuals. In the cortex, the deleted to total mtDNA ratio ranged from 0.00023 to 0.012 in 67-77 year old brains and up to 0.034 in subjects over 80. In the putamen, the deletion level ranged from 0.0016 to 0.010 in 67 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
391
2
6

Year Published

1993
1993
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 838 publications
(419 citation statements)
references
References 30 publications
20
391
2
6
Order By: Relevance
“…21 Heteroplasmic de novo deletions of the mtDNA are known to accumulate during life. 22,23 It has, however been less clear if the level of pathogenic mitochondrial point mutations increase or decrease with time. When performing a serial analysis of one patient with skeletal myopathy, the somatic heteroplasmic A12320G mutation in the tRNA Leu gene increased in skeletal muscle over a 12-year period from 69 to 90%.…”
Section: Discussionmentioning
confidence: 99%
“…21 Heteroplasmic de novo deletions of the mtDNA are known to accumulate during life. 22,23 It has, however been less clear if the level of pathogenic mitochondrial point mutations increase or decrease with time. When performing a serial analysis of one patient with skeletal myopathy, the somatic heteroplasmic A12320G mutation in the tRNA Leu gene increased in skeletal muscle over a 12-year period from 69 to 90%.…”
Section: Discussionmentioning
confidence: 99%
“…38 On the basis of postmortem studies it has also been reported that mtDNA 4977-bp deletions increased with age in brains postmortem. 39 More recently, a T414G transversion was found to increase with age in human fibroblast mtDNA. 40 Tanaka et al 41 sequenced the whole mtDNA genome in 11 healthy Japanese subjects more than 100 years old and compared these sequences with those of control subjects.…”
Section: Agingmentioning
confidence: 99%
“…Numerous studies have shown that mtDNA accumulates oxidative damage in an age-dependent manner in skeletal muscle (57)(58)(59), cardiac muscle (60-62), brain (63) and liver (64). Specifically, the increase in 8-oxoG levels in mtDNA with age appears to be a general phenomenon and has been reported by de Souza-Pinto et.…”
Section: Mitochondrial Dna Repair and Agingmentioning
confidence: 70%